Metaphysical Presuppositions of the Empirical Project of Nicholas of Cusa in Idiota de staticis experimentis - Senovsky, Jakub (Civilia, 2012)
Nicholas of Cusa is considered to be one of the first thinkers, who used the term "experiment" in the same way it is being used nowadays, especially in natural sciences. In my contribution, I would like to focus on specific metaphysical presuppositions, which allowed Cusanus to develop this almost "empirical philosophy" in Idiota de staticis experimentis. It will be showed that the empirical project of Cusa is fully dependent on his own explication of the Neo-platonism "metaphysics of the One".
Keywords: Empirical science; Experiment; Neo-Platonism; Cusanus